Kualitas Hard Skill Mahasiswa Trainee: Departemen Front Office pada Hotel Bintang Empat di Kota Bandung - Retha Syahvina Zahra; Vany Octaviany (Syntax Corporation, 2023)
Most of the Human Resources in the Hospitality Industry, particularly in the Front Office department, have limitations in terms of knowledge, competence, and technical skills in their work. This requires efforts to enhance their understanding of these aspects in their work, in order to improve the quality of the services provided and ensure the smooth operation of the hotel. The aim of this research is to determine the quality of hard skills of student trainees in the Front Office department at a four-star hotel in the city of Bandung and the efforts to enhance these skills. The method used is qualitative ethnography, involving observation, documentation, and interviews with the Front Office Manager (FOM), supervisors, and student trainees at the four-star hotels. The research locations include Four Points by Sheraton, The Jayakarta Hotel Bandung, and Grand Tjokro Hotel. Based on the analysis results, it was found that hard skills are formed through interactions between technical abilities, knowledge, and technological proficiency. Overall, this study found that student trainees have good knowledge, technical skills, and technological abilities in their work. Efforts to enhance the hard skills of student trainees in the Front Office department include providing training to improve additional skills such as time management, interpersonal communication, and problem-solving.